Plasma of electric arc discharge between copper electrodes in a gas flow - Babich, I.L.; Boretskij, V.F.; Veklich, A.N. (Вопросы атомной науки и техники, 2008)
Spectroscopy investigations of the thermal multicomponent plasma of the electric arc discharge between copper electrodes in carbon dioxide and argon flows were carried out. The technique of calculation of plasma equilibrium composition is discussed. The influence of hydrodynamic cooling of gas flow on the plasma state is estimated. It was assumed that the thermal dissociation of molecules of working gas play the key role in deviation from local thermodynamic equilibrium (LTE) in plasma. Спектроскопічними методами досліджено термічну багатокомпонентну плазму електродугового розряду між мідними електродами у потоках аргону та вуглекислого газу. Обговорюється методика розрахунку рівноважного складу плазми. Оцінений вплив гідродинамічного охолодження потоком газу на стан плазми. Припускається, що термічна дисоціація молекул робочого газу є основним механізмом відхилення від локальної термодинамічної рівноваги в плазмі. Спектроскопическими методами исследована термическая многокомпонентная плазма электродугового разряда между медными электродами в потоках аргона и углекислого газа. Обсуждается методика расчета равновесного состава плазмы. Оценено влияние гидродинамического охлаждения потоком газа на состояние плазмы. Предполагается, что термическая диссоциация молекул рабочего газа является основным механизмом отклонения от локального термодинамического равновесия в плазме.